Preparation method of aluminum-boron carbide-based composite adsorption material

CN122974263APending Publication Date: 2026-10-27HANGZHOU TAOFEILUN NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611077903.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明旨在解决现有铝碳化硼基气体吸附材料制备工艺复杂、活性组分成本高、高温制备过程中碳化硼与活性组分之间的界面相容性不足以及现有技术未涉及气态碘吸附应用的问题,提供一种工艺简单、能够通过化学吸附机制实现气态碘高效捕获的铝碳化硼基复合吸附材料及其制备方法

Benefits of technology

从组分角度看,本方案采用过渡金属粉末直接引入体系,与铝基体形成弥散强化相,改善碳化硼与铝基体之间的界面结合。碳化硼中的硼元素与过渡金属协同作用,在界面处构建化学吸附活性中心,实现对碘的有效捕获。造孔剂分解后完全逸出,不遗留固体残留物,保证了孔隙的纯净度。各组分功能分工明确:碳化硼主责化学吸附,过渡金属兼顾基体增强与辅助吸附,铝基体承担结构支撑。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses an aluminum-boron carbide-based composite adsorption material and a preparation method thereof, and belongs to the technical field of inorganic material preparation. The preparation method comprises the following steps: mixing boron carbide powder, a pore-forming agent, a transition metal powder and a binder, adding an organic solvent to stir to obtain a mixed slurry; after drying, pressure forming is performed to obtain a blank; pre-sintering is performed in an inert gas atmosphere to obtain a porous preform; after the porous preform is crushed, the aluminum powder is mixed or layered and alternately filled, and then re-pressing and secondary sintering are performed to obtain the aluminum-boron carbide-based composite adsorption material. The one-step pore-forming method combined with the secondary sintering process replaces the two-step pore-forming and pressureless infiltration process in the prior art, the transition metal powder is used to replace the copper-based hollow carbon microspheres, the process flow is simplified, the aluminum distribution uniformity is improved, and the aluminum-boron carbide-based composite adsorption material can be used for adsorbing gaseous iodine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of inorganic material preparation technology, specifically to an aluminum boron carbide-based composite adsorbent material and its preparation method. Background Technology

[0002] Radioactive iodine is characterized by its long radioactive half-life, high biotoxicity, and volatility. Existing gaseous iodine adsorbents mainly employ systems such as impregnated activated carbon, silver-based molecular sieves, and metal-organic frameworks (MOFs). Impregnated activated carbon is currently the most widely used iodine adsorbent in nuclear facility ventilation systems; however, its adsorption performance significantly decreases under high temperature and humidity conditions, and activated carbon itself is flammable, posing a combustion risk in nuclear accident scenarios. Silver-based molecular sieves have high adsorption capacity, but the high price of silver keeps costs high. While MOFs possess high specific surface area and tunable pore structure, their hydrothermal and radiation stability are insufficient, making them unsuitable for long-term use in the harsh environments of the nuclear industry. Therefore, novel adsorbents possessing good thermal stability, radiation stability, and iodine affinity have become a research direction in this field. Aluminum-boron carbide composites combine the good toughness and processing properties of aluminum alloys with the high strength, high hardness, low density, and neutron absorption properties of boron carbide, showing broad application prospects in the nuclear industry, aerospace, and armor protection.

[0003] Patent CN120420953A discloses an aluminum boron carbide-based gas adsorbent material and its preparation method. It uses aluminum boron carbide as the framework and copper-based hollow carbon microspheres as the active component. First, the carbon microspheres are mixed with boron carbide powder, a pore-forming agent, and a binder, then pressed and sintered to obtain a first preform. Next, the preform is impregnated in a second pore-forming agent solution, and finally, the finished product is manufactured using a pressureless aluminum impregnation process. The resulting material exhibits high specific strength and high-temperature resistance. This method provides a feasible technical path for the application of aluminum boron carbide materials in the field of gas adsorption. However, it should be noted that this scheme employs a two-step pore-forming process: the first pore-forming agent is used to form initial pores, and the second pore-forming agent is introduced through solution impregnation to further increase porosity. The overall process is relatively complex and the production cycle is relatively long. Furthermore, the copper-based hollow carbon microspheres used need to be prepared separately through multiple processes such as hydrothermal carbonization of chitosan oligosaccharides and high-temperature calcination, increasing production costs in the raw material preparation stage and hindering large-scale promotion. In terms of application, this material is mainly targeted at hydrocarbons in automobile exhaust. It belongs to the adsorption of hydrocarbon organic gas molecules, and its mechanism of action is mainly physical adsorption and catalytic oxidation.

[0004] Patent CN120666189A discloses a method for preparing aluminum boron carbide composite materials. It uses an aluminum-based metal-organic framework (MOF) as the aluminum source and a boron-containing organic compound as the boron source. The boron-containing organic compound is loaded into the interlayer voids of the MOF using an in-situ reaction, followed by multi-stage calcination in various atmospheres to obtain an aluminum boron carbide material with an interpenetrating phase composite structure. This material is primarily targeted at applications requiring high mechanical properties and high-temperature resistance. This technical solution is innovative in the field of structural materials. However, its raw material system involves both MOFs and boron-containing organic compounds, resulting in higher costs and more complex synthesis steps. This differs significantly from the preparation routes of gas adsorption materials, and its product positioning focuses more on structural load-bearing and high-temperature resistance applications, rather than being designed for adsorption functions.

[0005] In summary, the existing preparation processes for aluminum boron carbide-based composite materials remain relatively cumbersome. To achieve high porosity by introducing a sufficient amount of pore-forming agent in a single step, the agent decomposes and generates gas during the gas production stage, leading to violent gas escape from the green body. At this point, the green body has not yet developed sufficient sintering strength, making it highly susceptible to expansion, deformation, blistering, and even cracking and collapse. Furthermore, current technologies primarily focus on the physical adsorption and catalytic oxidation of hydrocarbon organic gases, neglecting gaseous pollutants such as radioactive iodine that require chemical adsorption mechanisms. Effective solutions are also lacking for interfacial compatibility between boron carbide and the active components during high-temperature preparation, as well as for pore retention issues. Therefore, there is an urgent need to develop a relatively simplified, cost-effective method for preparing aluminum boron carbide-based composite adsorbent materials that can efficiently capture gaseous iodine through chemical adsorption. Summary of the Invention

[0006] This invention aims to address the problems of complex preparation processes, high cost of active components, insufficient interfacial compatibility between boron carbide and active components during high-temperature preparation, and the lack of application of gaseous iodine adsorption in existing technologies. It provides an aluminum boron carbide-based composite adsorbent material with a simple process that can achieve efficient capture of gaseous iodine through chemical adsorption mechanism, as well as its preparation method.

[0007] To achieve the above objectives, the present invention provides a method for preparing an aluminum boron carbide-based composite adsorbent material, characterized by comprising the following steps: Step 1: Mix boron carbide powder, pore-forming agent, transition metal powder and binder in a mass ratio of 40~60:10~25:5~15:2~8, add organic solvent, and mechanically stir for 15~45 minutes to obtain a mixed slurry; Step 2: After drying the mixed slurry obtained in Step 1, place it in a mold and press it into shape. The pressing pressure is 200~350MPa to obtain a green body. Step 3: Place the green body obtained in Step 2 in an atmosphere sintering furnace and pre-fire it under an inert gas atmosphere. Increase the temperature from room temperature to 350-450°C at a heating rate of 2-5°C / min and hold for 1-3 hours to allow the pore-forming agent to completely decompose and form a network of interconnected pores inside the green body. Then, continue to increase the temperature to 750-900°C at a heating rate of 3-6°C / min and hold for 2-4 hours to allow diffusion sintering between the boron carbide particles in the green body to form a porous preform with a certain strength. Step 4: After crushing the porous preform obtained in Step 3 to a particle size of 1-5 mm, mix it with aluminum powder at a mass ratio of 45-55:45-55. Press it again under a pressure of 100-200 MPa and perform secondary sintering under an argon atmosphere. Raise the temperature to 450-500℃ at 3-5℃ / min and hold for 1-3 hours. Then raise the temperature to 900-1000℃ at 3-5℃ / min and hold for 1-2 hours to allow the aluminum to melt and be evenly distributed in the pores of the preform. Then lower the temperature to 300℃ at a cooling rate of 1-3℃ / min and then let it cool naturally to room temperature.

[0008] In the preparation method of this invention, boron carbide powder provides boron as a chemical adsorption site for iodine, and at the same time, it acts as a reinforcing phase to improve the hardness and thermal stability of the material. However, excessive amount will lead to a decrease in the continuity of the aluminum matrix, resulting in molding difficulties. Transition metal powder improves the interfacial bonding between boron carbide and the aluminum matrix, and helps to enhance the chemical adsorption capacity for iodine. After the pore-forming agent decomposes, it leaves interconnected pores in the billet, providing channels for gas diffusion and aluminum liquid penetration. The binder ensures the green strength of the billet during the molding stage.

[0009] Step 3, the pre-firing process, is completed in two temperature stages to form pores and solidify the framework. The low-temperature stage (350-450℃) allows the pore-forming agent to completely decompose and escape, forming primary interconnected pores within the green body. The high-temperature stage (750-900℃) allows diffusion sintering between boron carbide particles, forming a porous framework. This temperature range balances the densification of the boron carbide framework with the suppression of transition metal interface reactions: below 750℃, the sintering neck is insufficiently developed; above 900℃, the reaction between boron carbide and the transition metal intensifies, generating metal boride impurities that consume effective boron sites. There is a synergistic relationship between the amount of pore-forming agent and the sintering regime. When the amount of pore-forming agent increases, the holding time in the low-temperature stage should be appropriately extended or the holding temperature increased to ensure that the pore-forming agent completely decomposes before entering the high-temperature stage, avoiding residual pore-forming agent from generating gas in the high-temperature stage and damaging the already formed pore structure.

[0010] In step 4, the porous preform is crushed, mixed with aluminum powder, repressed, and then sintered a second time. The aluminum powder removes surface adsorbates at 450-500℃ and establishes thermal equilibrium with the preform. After melting at 900-1000℃, it is uniformly filled into the pores of the preform by capillary force. At this point, the aluminum liquid has good fluidity, achieving sufficient filling, while the interfacial reaction between aluminum and boron carbide is relatively mild. Compared to the traditional method of placing aluminum powder above the preform for pressureless infiltration, crushing and mixing shortens the aluminum distribution path, improving the uniformity of aluminum distribution. The repressing pressure is controlled at 100-200 MPa. It is important to note that pressures exceeding 200 MPa may crush the existing porous framework structure, disrupting the interconnected pore network and reducing the uniformity of aluminum filling. The selection of transition metal powder is related to the sintering temperature; a transition metal system with low reactivity with boron carbide within the 750-900℃ range ensures that the boron carbide function is not compromised.

[0011] Preferably, the pore-forming agent in step 1 is selected from at least one of ammonium bicarbonate, urea, and ammonium oxalate.

[0012] Preferably, the transition metal powder in step 1 is selected from at least one of iron powder, cobalt powder, and nickel powder. All three belong to Group VIII and have low reactivity with boron carbide at sintering temperatures of 750~900℃. This can improve the interfacial bonding between the aluminum matrix and boron carbide while avoiding significant consumption of boron carbide.

[0013] Preferably, the adhesive in step 1 is selected from at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, and polyethylene glycol. The decomposition temperature window of the adhesive is related to the decomposition window of the pore-forming agent: the adhesive can maintain a certain interparticle bonding force during the stage of large-scale decomposition and gas generation of the pore-forming agent, providing temporary skeletal strength for the green body. After the nano-transition metal powder begins to form metal bridges in the later stage of the low-temperature period, the adhesive gradually decomposes and exits, achieving a smooth transition in the strength of the green body.

[0014] Preferably, in step 1, the average particle size of the boron carbide powder is 10-50 μm, and the average particle size of the transition metal powder is 50-200 nm. The particle sizes of the two powders are on different orders of magnitude, and the nanoscale transition metal powder can be adsorbed on the surface of the micron-sized boron carbide particles or fill the gaps between the particles, which is beneficial for its uniform dispersion in the matrix.

[0015] Preferably, in step 1, the organic solvent is selected from at least one of anhydrous ethanol, methanol, and isopropanol, and the amount added is 0.8 to 1.5 times the total mass of the solid powder.

[0016] Preferably, in step 1, the mass ratio of boron carbide powder, pore-forming agent, transition metal powder, and binder is 50:15:10:5. Under this ratio, the boron carbide framework exhibits good connectivity, providing ample chemisorption sites and aluminum melt permeation channels; the amount of pore-forming agent is moderate, resulting in porosity that meets gas diffusion requirements without causing insufficient continuity of the aluminum matrix due to excessive porosity; the transition metal powder forms a uniformly dispersed phase, and its auxiliary adsorption sites complement the main adsorption sites of boron carbide.

[0017] Preferably, the inert gas in step 3 is argon or nitrogen, and the gas flow rate is 100~300 mL / min.

[0018] Preferably, the pre-firing process in step 3 is as follows: the temperature is increased to 400℃ at 3℃ / min and held for 2 hours, then increased to 850℃ at 5℃ / min and held for 3 hours, and finally decreased to 300℃ at 2℃ / min and allowed to cool naturally. This process, through slow heating and holding at low temperatures, allows the pore-forming agent to decompose smoothly while the binder still acts as a skeleton; the medium-temperature stage rapidly passes through the 500~750℃ range to reduce the solid-phase reaction between boron carbide and the transition metal; the high-temperature stage provides sufficient holding time to form stable sintering necks between boron carbide particles; and the slow cooling releases thermal stress, preventing cracking of the preform.

[0019] This invention also proposes an aluminum boron carbide-based composite adsorbent material prepared by the above-described method. In this material, boron carbide particles form a porous framework, and the transition metal component synergistically provides chemisorption capacity for iodine with boron carbide. The material retains interconnected pores formed by the decomposition of the pore-forming agent, which constitute channels for gas molecules to diffuse into the material. The aluminum matrix, as a continuous phase, binds the boron carbide particles and the pore network into a whole, providing structural strength and thermal conductivity to the material.

[0020] The aluminum boron carbide-based composite adsorbent of the present invention is used for adsorbing gaseous iodine. Gaseous iodine includes molecular iodine and organic iodine, which may be released into the environment in gaseous form in the ventilation systems of nuclear fuel reprocessing plants and in nuclear accident emergency scenarios.

[0021] Compared to existing technologies, the advantages of this solution are: From a compositional perspective, this scheme directly introduces transition metal powder into the system, forming a dispersed reinforcing phase with the aluminum matrix and improving the interfacial bonding between boron carbide and the aluminum matrix. The boron element in boron carbide works synergistically with the transition metal to construct chemisorption active centers at the interface, achieving effective iodine capture. The pore-forming agent completely escapes after decomposition, leaving no solid residue and ensuring the purity of the pores. The functional division of each component is clear: boron carbide is primarily responsible for chemisorption, the transition metal serves as both matrix reinforcement and auxiliary adsorption, and the aluminum matrix provides structural support.

[0022] From a technological perspective, this solution employs a two-stage sintering method to replace the two-step pore-forming and pressureless infiltration process. After pre-firing to form a porous preform containing a pore-forming agent, the preform is crushed, mixed with aluminum powder, repressed, and then subjected to a second sintering. The molten aluminum powder, driven by capillary force, penetrates short-range into the gaps between preform particles and the internal pores, uniformly filling the gaps and avoiding the uneven filling and pore blockage problems caused by the long-range flow of molten aluminum from top to bottom in traditional pressureless infiltration. The sintering temperature range of the preform balances the sufficient sintering of the boron carbide framework with the suppression of transition metal interface reactions, while the second sintering temperature range ensures good fluidity of the molten aluminum and a mild degree of interface reaction. The crushing and mixing process shortens the aluminum distribution path, improves the uniformity of aluminum distribution, and reduces local defects. Detailed Implementation

[0023] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to specific examples. However, it should be understood that these embodiments are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this application.

[0024] In this embodiment, a method for preparing an aluminum boron carbide-based composite adsorbent material includes the following steps.

[0025] Step 1: Mix boron carbide powder, pore-forming agent, transition metal powder, and binder in a mass ratio of 40-60:10-25:5-15:2-8. The average particle size of the boron carbide powder is 10-50 μm. The pore-forming agent is selected from at least one of ammonium bicarbonate, urea, and ammonium oxalate. The transition metal powder is selected from at least one of iron powder, cobalt powder, and nickel powder, and the average particle size of the transition metal powder is 50-200 nm. The binder is selected from at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, and polyethylene glycol. Add the above components to a mixing container, and add an organic solvent, selected from at least one of anhydrous ethanol, methanol, and isopropanol. The amount of organic solvent added is 0.8-1.5 times the total mass of the boron carbide powder, pore-forming agent, transition metal powder, and binder. Start the mechanical stirring device and stir at a speed of 200-400 rpm for 15-45 minutes to obtain a uniformly dispersed slurry. During the stirring process, the binder gradually dissolves in the organic solvent. The active groups on its molecular chain form hydrogen bonds or physical adsorption with the polar sites on the surface of the powder particles, which encapsulate and bridge the boron carbide powder, pore-forming agent and transition metal powder together, preventing the components from re-aggregating after the solvent evaporates.

[0026] Step 2: Transfer the mixed slurry obtained in Step 1 to a drying container and dry it at 60-80℃ for 8-16 hours to allow the organic solvent to completely evaporate, obtaining a dried mixed powder. Place the dried mixed powder into a mold, put it on the worktable of a pressing and molding equipment, and apply a pressure of 200-350MPa for pressing and molding. After holding the pressure for 1-5 minutes, release the pressure and demold to obtain a green body with a certain shape and size. The shape and size of the green body are determined according to the requirements of the target adsorbent material. In this embodiment, the green body is a cylinder with a diameter of 20-50mm and a height of 10-30mm. When the pressing pressure is below 200MPa, the mechanical interlocking between powder particles is insufficient, resulting in low green strength and easy breakage during subsequent handling and sintering. When the pressing pressure is above 350MPa, the stress on the mold is too high, and the stress distribution inside the green body is uneven. After depressurization, delamination or micro-cracks may occur due to elastic aftereffects.

[0027] Step 3: Place the green body obtained in Step 2 into an atmosphere sintering furnace. After shutting down the furnace, start the vacuum pump to evacuate the furnace until the pressure inside the furnace is below 100 Pa. Then, introduce an inert gas to atmospheric pressure. The inert gas can be argon or nitrogen, and the gas flow rate should be controlled at 100~300 mL / min. Repeat the evacuation and inert gas introduction operation two to three times to fully remove the air from the furnace. Start the heating program and raise the temperature from room temperature to 350~450℃ at a rate of 2~5℃ / min. Hold at this temperature for 1~3 hours. During this heating period, the pore-forming agent gradually decomposes into gaseous products after reaching its decomposition temperature and escapes from the green body, leaving interconnected pores inside the green body. Ammonium bicarbonate begins to decompose into ammonia and carbon dioxide at 36~60℃, urea decomposes into ammonia and isocyanate at 135~200℃, isocyanate further decomposes into carbon dioxide and ammonia, and ammonium oxalate decomposes into carbon monoxide, carbon dioxide, ammonia, and water vapor at 250~300℃. The binder gradually decomposes into gaseous products within the temperature range of 300-400℃. Holding at this temperature for 1-3 hours ensures that both the pore-forming agent and the binder have fully decomposed. Then, the temperature is increased from 350-450℃ to 750-900℃ at a rate of 3-6℃ / min, and held at this temperature for 2-4 hours. During this heating phase, solid-state diffusion and sintering begin between boron carbide particles in the preform and between boron carbide particles and transition metal powder. The necks between particles gradually grow, forming a porous framework structure with a certain strength. Holding at this temperature for 2-4 hours allows the sintering process to proceed fully, while controlling the holding time to limit the degree of interfacial reaction between boron carbide and transition metal powder. Then, the temperature is reduced from 750-900℃ to 300℃ at a rate of 1-3℃ / min, and then the heating power is turned off, allowing the furnace to cool naturally to room temperature, resulting in a porous preform. Controlling the cooling rate within the range of 1-3℃ / min is to avoid cracking of the preform due to thermal stress concentration during the cooling process. During the cooling process, keep the inert gas flowing continuously until the furnace temperature drops below 100°C before shutting off the gas.

[0028] Step 4: Crush the porous preform obtained in Step 3. The particle size of the crushed particles is 1-5 mm. Weigh the crushed porous preform particles and aluminum powder. The aluminum powder is industrial pure aluminum powder or aluminum alloy powder with an average particle size of 10-50 μm. The mass ratio of the crushed porous preform to the aluminum powder is 45-55:45-55. Mix the crushed porous preform particles and aluminum powder evenly and load them into a mold. Then, repress the mixture at a pressure of 100-200 MPa to obtain a secondary green body. Place the secondary green body in an atmosphere sintering furnace. After shutting down the furnace, start the vacuum pump to evacuate the furnace until the pressure inside the furnace is below 10 Pa. Then, introduce high-purity argon gas to atmospheric pressure. The purity of the argon gas should not be less than 99.999%. Initiate the heating program, raising the temperature to 450-500℃ at a rate of 3-5℃ / min, and hold for 1-3 hours. This allows the moisture and trace organic matter adsorbed on the surface of the aluminum powder to evaporate, while simultaneously establishing a preliminary thermal equilibrium between the aluminum powder particles and between the aluminum powder and the preform particles. Then, continue raising the temperature at a rate of 3-5℃ / min to 900-1000℃, and hold for 1-2 hours. During this heating process, the aluminum powder begins to melt at approximately 660℃. Because the aluminum powder has already been uniformly mixed or layered with the preform particles in the secondary blank, the molten aluminum can fill the gaps between the preform particles and the interconnected pores within the particles without requiring long-distance migration. Holding at 900-1000℃ reduces the viscosity of the molten aluminum, allowing it to further penetrate into the pores within the preform particles under capillary force. Holding for 1-2 hours ensures uniform distribution and sufficient penetration of the molten aluminum. The temperature was then reduced from 900-1000℃ to 300℃ at a rate of 1-3℃ / min. The heating power was then turned off, allowing the furnace to cool naturally to room temperature, thus obtaining the aluminum boron carbide-based composite adsorbent material. Argon gas was continuously supplied during the cooling process until the furnace temperature dropped below 100℃ before the gas supply was shut off. Example 1:

[0029] A method for preparing an aluminum boron carbide-based composite adsorbent material includes the following steps.

[0030] Step 1: Mix boron carbide powder with an average particle size of 30 μm, ammonium bicarbonate, iron powder with an average particle size of 125 nm and polyvinyl alcohol in a mass ratio of 50:17.5:10:5. Add anhydrous ethanol at a mass ratio of 1.15 times the total mass of the mixture and stir at a speed of 300 rpm for 30 minutes to obtain a mixed slurry.

[0031] Step 2: Dry the mixed slurry obtained in Step 1 at 70℃ for 12 hours until the anhydrous ethanol is completely evaporated, resulting in a dried mixed powder. The dried mixed powder is then placed into a mold, pressurized at 275MPa, and held under pressure for 3 minutes before being depressurized to obtain a cylindrical blank with a diameter of 35mm and a height of 20mm.

[0032] Step 3: Place the preform obtained in Step 2 in an atmosphere sintering furnace. Evacuate the furnace until the pressure inside is below 100 Pa, then introduce argon gas to atmospheric pressure at a flow rate of 200 mL / min. Repeat the evacuation and gas introduction process three times. Increase the temperature to 400℃ at 3.5℃ / min and hold for 2 hours, then increase the temperature to 825℃ at 4.5℃ / min and hold for 3 hours. Decrease the temperature to 300℃ at 2℃ / min, and allow it to cool naturally to room temperature to obtain a porous preform. Maintain argon gas flow during the cooling process, and shut off the gas supply once the furnace temperature drops below 100℃.

[0033] Step 4: The porous preform obtained in Step 3 is crushed to a particle size of 3 mm, mixed evenly with industrial pure aluminum powder with an average particle size of 30 μm at a mass ratio of 50:50, and then placed into a mold. A pressure of 150 MPa is applied, and the mixture is re-pressed to obtain a secondary preform. The secondary preform is placed in an atmosphere sintering furnace, and after evacuating the furnace until the pressure inside the furnace is below 10 Pa, high-purity argon gas with a purity of not less than 99.999% is introduced to atmospheric pressure. The temperature is increased to 475℃ at 4℃ / min and held for 2 hours, then increased to 950℃ at 4℃ / min and held for 1.5 hours, and then decreased to 300℃ at 2℃ / min. The mixture is then allowed to cool naturally to room temperature to obtain an aluminum boron carbide-based composite adsorbent material. Argon gas is maintained during the cooling process, and the gas is shut off once the furnace temperature drops below 100℃. Example 2:

[0034] A method for preparing an aluminum boron carbide-based composite adsorbent material includes the following steps.

[0035] Step 1: Mix boron carbide powder with an average particle size of 10 μm, ammonium bicarbonate, iron powder with an average particle size of 50 nm and polyvinyl alcohol in a mass ratio of 40:10:5:2. Add anhydrous ethanol at 0.8 times the total mass of the mixture and stir at 200 rpm for 15 minutes to obtain a mixed slurry.

[0036] Step 2: The mixed slurry obtained in Step 1 is dried at 60℃ for 8 hours to completely evaporate the anhydrous ethanol, resulting in a dried mixed powder. The dried mixed powder is then placed into a mold, pressurized at 200MPa, and held under pressure for 1 minute before being depressurized to obtain a cylindrical blank with a diameter of 20mm and a height of 10mm.

[0037] Step 3: The preform obtained in Step 2 is placed in an atmosphere sintering furnace. Vacuum is applied until the furnace pressure is below 100 Pa, then argon gas is introduced to atmospheric pressure at a flow rate of 100 mL / min. This vacuuming and gas introduction process is repeated three times. The temperature is increased to 350℃ at a rate of 2℃ / min and held for 1 hour, then increased to 750℃ at a rate of 3℃ / min and held for 2 hours, and finally decreased to 300℃ at a rate of 1℃ / min. The preform is then allowed to cool naturally to room temperature to obtain a porous preform. Argon gas is maintained during the cooling process, and the gas supply is shut off once the furnace temperature drops below 100℃.

[0038] Step 4: The porous preform obtained in Step 3 is crushed to a particle size of 1 mm, mixed evenly with industrial pure aluminum powder with an average particle size of 10 μm at a mass ratio of 45:55, and then loaded into a mold. A pressure of 100 MPa is applied, and the mixture is re-pressed to obtain a secondary preform. The secondary preform is placed in an atmosphere sintering furnace, and after evacuating the furnace until the pressure inside the furnace is below 10 Pa, high-purity argon gas with a purity of not less than 99.999% is introduced to atmospheric pressure. The temperature is increased to 450℃ at 3℃ / min and held for 1 hour, then increased to 900℃ at 3℃ / min and held for 1 hour, and then decreased to 300℃ at 1℃ / min. The mixture is then allowed to cool naturally to room temperature to obtain an aluminum boron carbide-based composite adsorbent material. Argon gas is maintained during the cooling process, and the gas is shut off once the furnace temperature drops below 100℃. Example 3:

[0039] A method for preparing an aluminum boron carbide-based composite adsorbent material includes the following steps.

[0040] Step 1: Mix boron carbide powder with an average particle size of 50 μm, ammonium bicarbonate, iron powder with an average particle size of 200 nm, and polyvinyl alcohol in a mass ratio of 60:25:15:8. Add anhydrous ethanol at 1.5 times the total mass of the mixture and stir at 400 rpm for 45 minutes to obtain a mixed slurry.

[0041] Step 2: The mixed slurry obtained in Step 1 is dried at 80℃ for 16 hours until the anhydrous ethanol is completely evaporated, resulting in a dried mixed powder. The dried mixed powder is then placed into a mold, pressurized at 350MPa, and held under pressure for 5 minutes before being depressurized to obtain a cylindrical blank with a diameter of 50mm and a height of 30mm.

[0042] Step 3: The preform obtained in Step 2 is placed in an atmosphere sintering furnace. Vacuum is applied until the furnace pressure is below 100 Pa, then argon gas is introduced to atmospheric pressure at a flow rate of 300 mL / min. This vacuuming and gas introduction process is repeated three times. The temperature is increased to 450℃ at 5℃ / min and held for 3 hours, then increased to 900℃ at 6℃ / min and held for 4 hours, and finally decreased to 300℃ at 3℃ / min. The preform is then allowed to cool naturally to room temperature to obtain a porous preform. Argon gas is maintained during the cooling process, and the gas supply is shut off once the furnace temperature drops below 100℃.

[0043] Step 4: The porous preform obtained in Step 3 is crushed to a particle size of 5 mm, mixed evenly with industrial pure aluminum powder with an average particle size of 50 μm at a mass ratio of 55:45, and then placed into a mold. A pressure of 200 MPa is applied, and the mixture is re-pressed to obtain a secondary preform. The secondary preform is placed in an atmosphere sintering furnace, and after evacuating the furnace until the pressure inside the furnace is below 10 Pa, high-purity argon gas with a purity of not less than 99.999% is introduced to atmospheric pressure. The temperature is increased to 500℃ at 5℃ / min and held for 3 hours, then increased to 1000℃ at 5℃ / min and held for 2 hours, and then decreased to 300℃ at 3℃ / min. The mixture is then allowed to cool naturally to room temperature to obtain an aluminum boron carbide-based composite adsorbent material. Argon gas is maintained during the cooling process, and the gas is shut off once the furnace temperature drops below 100℃. Example 4:

[0044] A method for preparing an aluminum boron carbide-based composite adsorbent material includes the following steps.

[0045] Step 1: Mix boron carbide powder with an average particle size of 20 μm, urea, cobalt powder with an average particle size of 80 nm, and sodium carboxymethyl cellulose in a mass ratio of 55:20:8:4. Add anhydrous ethanol at 1.2 times the total mass of the mixture and stir at 250 rpm for 35 minutes to obtain a mixed slurry.

[0046] Step 2: The mixed slurry obtained in Step 1 is dried at 65℃ for 14 hours to completely evaporate the anhydrous ethanol, resulting in a dried mixed powder. The dried mixed powder is then placed into a mold, pressurized at 250MPa, and held under pressure for 4 minutes before being depressurized to obtain a cylindrical blank with a diameter of 30mm and a height of 25mm.

[0047] Step 3: The green body obtained in Step 2 is placed in an atmosphere sintering furnace. Vacuum is drawn until the furnace pressure is below 100 Pa, then nitrogen gas is introduced to atmospheric pressure at a flow rate of 150 mL / min. This vacuuming and gas introduction process is repeated three times. The temperature is increased to 420℃ at 4℃ / min and held for 2.5 hours, then increased to 780℃ at 5℃ / min and held for 3.5 hours, and finally decreased to 300℃ at 1.5℃ / min. The mixture is then allowed to cool naturally to room temperature to obtain a porous preform. Nitrogen gas is maintained during the cooling process, and the gas supply is shut off once the furnace temperature drops below 100℃.

[0048] Step 4: The porous preform obtained in Step 3 is crushed to a particle size of 2 mm, mixed evenly with aluminum alloy powder with an average particle size of 20 μm at a mass ratio of 48:52, and then placed into a mold. A pressure of 120 MPa is applied, and the mixture is re-pressed to obtain a secondary blank. The secondary blank is placed in an atmosphere sintering furnace, and after evacuating the furnace until the pressure inside the furnace is below 10 Pa, high-purity argon gas with a purity of not less than 99.999% is introduced to atmospheric pressure. The temperature is increased to 480℃ at 3.5℃ / min and held for 1.5 hours, then increased to 920℃ at 4.5℃ / min and held for 1.5 hours, and then decreased to 300℃ at 1.5℃ / min. The mixture is then allowed to cool naturally to room temperature to obtain an aluminum boron carbide-based composite adsorbent material. Argon gas is maintained during the cooling process, and the gas is shut off once the furnace temperature drops below 100℃. Example 5:

[0049] A method for preparing an aluminum boron carbide-based composite adsorbent material includes the following steps.

[0050] Step 1: Mix boron carbide powder with an average particle size of 40 μm, ammonium oxalate, nickel powder with an average particle size of 150 nm, and polyethylene glycol in a mass ratio of 45:12:12:6. Add anhydrous ethanol at a mass ratio of 1.0 times the total mass of the mixture and stir at a speed of 350 rpm for 25 minutes to obtain a mixed slurry.

[0051] Step 2: The mixed slurry obtained in Step 1 is dried at 75℃ for 10 hours until the anhydrous ethanol is completely evaporated, resulting in a dried mixed powder. The dried mixed powder is then placed into a mold, pressurized at 300MPa, and held under pressure for 2 minutes before being depressurized to obtain a cylindrical blank with a diameter of 40mm and a height of 15mm.

[0052] Step 3: The preform obtained in Step 2 is placed in an atmosphere sintering furnace. After evacuating the furnace until the pressure inside is below 100 Pa, argon gas is introduced to atmospheric pressure at a flow rate of 250 mL / min. This evacuation and gas introduction process is repeated three times. The temperature is increased to 380℃ at 2.5℃ / min and held for 1.5 hours, then increased to 870℃ at 3.5℃ / min and held for 2.5 hours. The temperature is then decreased to 300℃ at 2.5℃ / min and allowed to cool naturally to room temperature to obtain a porous preform. Argon gas is maintained during the cooling process, and the gas supply is shut off once the furnace temperature drops below 100℃.

[0053] Step 4: The porous preform obtained in Step 3 is crushed to a particle size of 4 mm and mixed evenly with industrial pure aluminum powder with an average particle size of 40 μm at a mass ratio of 52:48. The mixture is then placed into a mold and re-pressed under a pressure of 180 MPa to obtain a secondary preform. The secondary preform is placed in an atmosphere sintering furnace, and after evacuating the furnace until the pressure inside the furnace is below 10 Pa, high-purity argon gas with a purity of not less than 99.999% is introduced to atmospheric pressure. The temperature is increased to 460℃ at 4.5℃ / min and held for 2.5 hours, then increased to 980℃ at 3.5℃ / min and held for 1 hour, and then decreased to 300℃ at 2.5℃ / min. The mixture is then allowed to cool naturally to room temperature to obtain the aluminum boron carbide-based composite adsorbent material. Argon gas is maintained during the cooling process, and the gas is shut off once the furnace temperature drops below 100℃.

[0054] Comparative Example 1 The difference from Example 1 is that the adhesive is replaced with paraffin wax instead of polyvinyl alcohol.

[0055] Comparative Example 2 The difference from Example 1 is that the transition metal powder iron powder was completely removed and its mass fraction was distributed to boron carbide and pore-forming agent in proportion.

[0056] Comparative Example 3 The difference from Example 1 is that in step 1, the particle size of the transition metal powder iron powder is 5 μm.

[0057] Comparative Example 4 The difference from Example 1 is that in step 1, copper powder is used instead of iron powder of equal mass.

[0058] Comparative Example 5 The difference from Example 1 is that the amount of boron carbide powder used is 65 parts, and the amount of pore-forming agent is adjusted to 25 parts.

[0059] Comparative Example 6 The difference from Example 1 is that in step 3, the heating rate in the low-temperature section is 1℃ / min.

[0060] Comparative Example 7 The difference from Example 1 is that in step 3, the heating rate in the low-temperature section is 8°C / min.

[0061] Comparative Example 8 The difference from Example 1 is that in step 3, the temperature of the high-temperature section is 1000°C.

[0062] Comparative Example 9 The difference from Example 1 is that in step 4, the temperature of the secondary sintering high-temperature section is 800°C.

[0063] Comparative Example 10 The difference from Example 1 is that in step 1, the mass fraction of the pore-forming agent ammonium bicarbonate is 35 parts.

[0064] Comparative Example 11 The difference from Example 1 is that in step 3, the heat preservation time of the high-temperature section is 0.5 hours.

[0065] The samples prepared in Examples 1-3 and Comparative Examples 1-11 were subjected to relevant performance tests. The corresponding test methods are shown in Table 1, and the test results are shown in Table 2.

[0066] Table 1 Detection Methods Specific surface area Referring to the detection method in GB / T 19587-2017, "Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method", approximately 0.5 g of the aluminum boron carbide-based composite adsorbent material obtained in the examples and comparative examples was degassed under vacuum at 300°C for 3 hours. Using nitrogen as the adsorbate, the adsorption amount was measured at different relative pressures at liquid nitrogen temperature of 77.3 K, and the specific surface area was calculated based on BET theory. Apparent porosity <![CDATA[Refer to the test method in GB / T 1966-2024, "Porous Ceramics - Determination of Apparent Porosity and Bulk Density". The porous preforms and final products obtained in Step 3 of the Examples and Comparative Examples are processed into cubic specimens with a side length of about 20 mm, dried at 110°C to constant weight, and then weighed to obtain the dry weight m1. The specimens are placed in distilled water and boiled for 4 hours to fully saturate the pores, then taken out to weigh the mass m2 of the saturated specimen in air, and then the mass m3 of the saturated specimen in water is weighed. The apparent porosity is calculated according to the formula P=(m2-m1) / (m2-m3)×100%.]]> Iodine adsorption capacity <![CDATA[With reference to the principle for determination of iodine adsorption value specified in GB / T 12496.8-2015 and GB / T 7702.7-2023, the following method is established in combination with the characteristics of the present material. The finished aluminum boron carbide-based composite adsorbent materials obtained in the Examples and Comparative Examples are taken, crushed and sieved to a particle size of 0.5 to 1.0 mm. About 1 g of the sample is placed in a quartz tube adsorber, and pretreated for 2 hours under nitrogen purge at 100°C to remove surface adsorbates. Elemental iodine is placed at the bottom of a constant-temperature blast drying oven, and volatilized at a constant temperature of 80°C to generate iodine vapor with a stable concentration, wherein the initial iodine vapor concentration is controlled at 200 ppm±20 ppm. The sample is exposed to an iodine vapor atmosphere at an adsorption temperature of 80°C for an adsorption time of 24 hours. After the adsorption is completed, the sample is taken out, sealed and cooled to room temperature, and then weighed for mass. The iodine adsorption capacity is calculated according to the formula Q=(m2-m1) / m1, and the unit of Q is mg / g. Meanwhile, the adsorbed sample is purged with nitrogen for 1 hour, and the ratio of the chemisorption amount to the total adsorption amount is measured.]]> iodine adsorption performance retention rate under high temperature and high humidity conditions <![CDATA[Take the finished aluminum boron carbide-based composite adsorption materials obtained in the examples and comparative examples, and measure the initial iodine adsorption capacity Q0 under normal temperature, normal pressure and dry conditions according to the above test method for iodine adsorption capacity. Take another sample from the same batch and place it in a constant temperature and humidity chamber at a temperature of 70°C±2°C, a relative humidity of 95%±2%, for a treatment time of 72 hours. After taking it out, dry it at 80°C for 2 hours to remove the moisture adsorbed on the surface, and then measure the iodine adsorption capacity Q1 after high temperature and high humidity treatment by the same method. The iodine adsorption performance retention rate is calculated according to the formula R=Q1 / Q0×100%.]]> compressive strength Referring to the testing methods in GB / T 31930-2015, "Ductility Tests of Metallic Materials: Compression Tests of Porous and Honeycomb Metals," the finished aluminum boron carbide-based composite adsorbent material obtained in the examples and comparative examples was processed into cylindrical specimens with a diameter of 20 mm and a height of 30 mm. The end faces of the specimens should be flat and parallel. A universal testing machine was used to apply a compressive load at a loading rate of 0.5 mm / min until the specimen failed, and the maximum compressive load F was recorded. The compressive strength was calculated using the formula σ = F / A, where A is the initial cross-sectional area of ​​the specimen, and σ is in MPa. Bending strength <![CDATA[Refer to the test methods in GB / T 1965-2023, "Test Method for Flexural Strength of Porous Ceramics at Room Temperature" and the corresponding principles in GB / T 232-2010. Take the finished aluminum boron carbide-based composite adsorption materials obtained in the Examples and Comparative Examples, process them into rectangular specimens with a length of 50mm, a width of 10mm and a height of 4mm, set the span to 40mm, and perform the test on a universal material testing machine using the three-point bending method. The loading rate is 0.5mm / min, and the maximum load F at fracture is recorded. The flexural strength is calculated according to the formula σ=3FL / (2bh 2 ), where F is the fracture load, L is the span, b is the width of the specimen, h is the height of the specimen, and the unit of σ is MPa.]]>

[0067] Table 2. Test Data for Examples and Comparative Examples Example 1 78.5 42.3 186.2 91.7 134.5 82.3 Example 2 56.2 33.8 148.5 87.2 156.8 95.1 Example 3 94.7 49.1 212.8 88.5 108.3 67.4 Example 4 82.3 44.6 191.5 90.8 128.7 78.6 Example 5 68.7 37.5 172.4 89.3 141.2 86.8 Comparative Example 1 31.6 18.2 72.4 76.3 52.6 33.5 Comparative Example 2 75.8 40.7 98.3 65.4 128.4 78.2 Comparative Example 3 74.2 40.1 152.7 84.1 96.2 58.7 Comparative Example 4 76.5 41.2 112.6 71.8 131.6 79.5 Comparative Example 5 — — 157.3 83.2 — — Comparative Example 6 76.8 41.5 179.5 90.2 131.2 80.1 Comparative Example 7 42.3 24.6 98.7 79.8 78.5 48.3 Comparative Example 8 71.5 39.8 112.4 73.6 118.6 72.4 Comparative Example 9 77.2 41.8 165.8 86.5 84.3 51.2 Comparative Example 10 118.6 56.3 195.7 82.1 43.7 27.6 Comparative Example 11 75.1 40.5 170.3 88.3 97.5 59.8 This invention addresses the problems of complex processes, long production cycles, high raw material preparation costs, and unfavorable conditions for large-scale production in the existing two-step pore-forming method combined with copper-based hollow carbon microspheres commonly used in the preparation of aluminum boron carbide-based gas adsorbent materials. It also fills the application gap of existing technologies, which mainly focus on the physical adsorption and catalytic oxidation of hydrocarbon organic gases and have not yet addressed the need for radioactive iodine chemical adsorption. Furthermore, it responds to a long-standing technical obstacle in this field, namely the inherent risk of expansion, deformation, and cracking during the gas generation stage of pore-forming agent decomposition within the blank strength vacuum period. This invention provides a technical solution that simplifies the process and achieves uniform aluminum distribution by combining a one-step pore-forming method with a secondary sintering process.

[0068] The performance of Examples 1 to 3 is significantly better than that of the comparative examples. Example 1 exhibits the most balanced overall performance, with an iodine adsorption capacity of 186.2 mg / g, a high-temperature and high-humidity retention rate of 91.7%, and compressive and flexural strengths meeting application requirements. Example 2, due to its lower proportion of boron carbide and pore-forming agent, has the lowest specific surface area and iodine adsorption capacity among the examples, but its relatively higher aluminum matrix proportion results in the highest compressive and flexural strengths among the three. This indicates that appropriately reducing the amount of boron carbide and pore-forming agent is beneficial to improving the material's density and mechanical strength, but at the cost of some adsorption performance. Example 3, due to its higher proportion of boron carbide and pore-forming agent, has the highest specific surface area and iodine adsorption capacity among the three, but its compressive and flexural strengths are the lowest, indicating a trade-off between high porosity and high strength. Example 4 uses urea as the pore-forming agent and cobalt powder as the transition metal powder, with various process parameters taken in alternating ways. It achieves an iodine adsorption capacity of 191.5 mg / g and a high-temperature and high-humidity retention rate of 90.8%, similar to Example 1, demonstrating good overall performance. Example 5 uses ammonium oxalate as a pore-forming agent and nickel powder as a transition metal powder, with a specific surface area of ​​68.7 m² / g, an iodine adsorption capacity of 172.4 mg / g, and mechanical properties between those of Examples 1 and 2. Data from Examples 4 and 5 show that, within the parameter range defined by this invention, different combinations of pore-forming agents, transition metal powders, and binders can achieve good combined adsorption and mechanical properties. This scheme exhibits good component adaptability and process tolerance. Example 1, through median proportions and an optimized sintering regime, achieved the optimal balance between adsorption and mechanical properties. The mechanism is as follows: the pore-forming agent decomposes to form interconnected pores; boron carbide particles form a porous framework through sintering; transition metal powder and boron carbide form chemical adsorption active centers at the interface; and aluminum powder melts and uniformly fills the pores, ultimately achieving a synergistic effect of physical and chemical adsorption.

[0069] Compared to the examples, in Comparative Example 1, replacing the binder with paraffin wax instead of polyvinyl alcohol resulted in a significant decrease in iodine adsorption capacity to 72.4 mg / g, compressive strength to 52.6 MPa, and flexural strength to 33.5 MPa. This indicates that paraffin wax cannot provide sufficient temporary bonding strength to the billet during the gas generation stage of the pore-forming agent decomposition, leading to pore structure collapse. Furthermore, the paraffin wax decomposition residue affects the filling effect of the molten aluminum on the pores.

[0070] In Comparative Example 2, after complete removal of the transition metal powder, the iodine adsorption capacity decreased to 98.3 mg / g, and the high-temperature and high-humidity retention rate decreased to 65.4%, a significant decrease compared to Example 1. This indicates that in the absence of transition metal powder, the material lacks effective chemical adsorption sites, and adsorption behavior is mainly physical adsorption. Physical adsorption is easily desorbed under high-temperature and high-humidity conditions. Simultaneously, the mechanical properties also decreased, indicating that the transition metal powder has a reinforcing effect on the matrix.

[0071] In Comparative Example 3, after increasing the particle size of the transition metal powder to 5 μm, the iodine adsorption capacity decreased to 152.7 mg / g, the compressive strength decreased to 96.2 MPa, and the flexural strength decreased to 58.7 MPa, all significantly lower than in Example 1. This indicates that the particle size of the transition metal powder is crucial to its functionality. When the particle size is too large, the interfacial reaction with boron carbide at the sintering temperature is insufficient, the number of chemisorption sites decreases, and the larger particles are unevenly dispersed in the matrix, leading to a decline in mechanical properties.

[0072] In Comparative Example 4, after replacing iron powder with an equal mass of copper powder, the iodine adsorption capacity decreased to 112.6 mg / g, and the high temperature and high humidity retention rate decreased to 71.8%. This indicates that copper powder cannot replace iron powder in forming an effective chemical adsorption active center with boron carbide, proving that the transition metal powders (iron, cobalt, nickel) selected in this scheme are irreplaceable for achieving high iodine adsorption performance.

[0073] In Comparative Example 5, when the amount of boron carbide powder was increased to 65 parts, the iodine adsorption capacity was 157.3 mg / g, the compressive strength decreased significantly, and the green body cracked during molding, making it impossible to obtain a complete sample that met the test size requirements for specific surface area and apparent porosity testing. This indicates that when the amount of boron carbide exceeds the limit, the material's molding performance and mechanical integrity are severely degraded.

[0074] When the heating rate in the low-temperature section of Comparative Example 6 was reduced to 1°C / min, the performance characteristics remained largely unchanged compared to Example 1, with only a slight decrease in specific surface area and apparent porosity. However, the process cycle was significantly extended. This indicates that an excessively slow heating rate does not significantly improve performance but instead reduces production efficiency.

[0075] In Comparative Example 7, when the heating rate in the low-temperature section increased to 8℃ / min, the specific surface area decreased to 42.3 m². 2 The apparent porosity decreased to 24.6%, the iodine adsorption capacity decreased to 98.7 mg / g, and the mechanical properties also decreased significantly. This indicates that when the heating rate is too fast, the concentrated gas production of the pore-forming agent exceeds the capacity of the green body, leading to the destruction of the pore structure and the generation of cracks, thus proving the rationality of the upper limit of the heating rate in this scheme.

[0076] In Comparative Example 8, after the temperature in the high-temperature section was raised to 1000℃, the iodine adsorption capacity decreased to 112.4 mg / g, and the high-temperature and high-humidity retention rate decreased to 73.6%. This indicates that excessively high sintering temperatures will intensify the reaction between boron carbide and transition metals, consume effective boron sites, and weaken the chemisorption capacity.

[0077] In Comparative Example 9, when the secondary sintering temperature was reduced to 800℃, the compressive strength decreased to 84.3 MPa and the flexural strength decreased to 51.2 MPa, indicating a significant decline in mechanical properties. This suggests that when the sintering temperature is too low, the aluminum melt has insufficient fluidity, making it difficult to fully fill the pores of the preform, resulting in insufficient material densification.

[0078] In Comparative Example 10, when the amount of pore-forming agent was increased to 35 parts, the specific surface area abnormally increased to 118.6 m². 2 The apparent porosity increased to 56.3% per g, but the compressive strength plummeted to 43.7 MPa and the flexural strength dropped to 27.6 MPa. This indicates that excessive pore-forming agent led to overdevelopment of pores, damaging the structural integrity and failing to meet the application requirements.

[0079] In Comparative Example 11, when the high-temperature holding time was shortened to 0.5 hours, the compressive strength decreased to 97.5 MPa and the flexural strength decreased to 59.8 MPa. This indicates that insufficient holding time leads to incomplete sintering of the boron carbide skeleton, resulting in insufficient strength development of the preform and affecting subsequent processes and the mechanical properties of the final product.

[0080] The above comparisons fully demonstrate that the component range and process conditions defined in this invention have clear critical significance. Any deviation from the range defined in this invention, such as the type of binder, the presence and particle size range of the transition metal powder, the amount of boron carbide, the upper and lower limits of the heating rate in the low-temperature section, the upper and lower limits of the temperature in the high-temperature section, the upper limit of the pore-forming agent dosage, or the lower limit of the holding time in the high-temperature section, will lead to a significant deterioration in adsorption performance or mechanical properties. This indicates that the parameter design of this scheme is reasonable, and the various process conditions have good matching.

[0081] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A method for preparing an aluminum boron carbide-based composite adsorbent, characterized in that, The preparation method includes the following steps: Step 1: Mix boron carbide powder, pore-forming agent, transition metal powder and binder in a mass ratio of 40~60:10~25:5~15:2~8, add organic solvent, and mechanically stir for 15~45 minutes to obtain a mixed slurry; Step 2: After drying the mixed slurry obtained in Step 1, place it in a mold and press it to form a green body; Step 3: Place the green body obtained in Step 2 in an atmosphere sintering furnace, heat it to 750~900℃ under an inert gas atmosphere for pre-firing, and hold it for 2~4 hours to obtain a porous preform. Step 4: After crushing the porous preform obtained in Step 3, mix it with aluminum powder at a mass ratio of 45~55:45~55 and repress it. Under an argon atmosphere, heat it to 900~1000℃ and hold it for 1~2 hours to perform secondary sintering. After cooling to room temperature, the aluminum boron carbide-based composite adsorbent material is obtained.

2. The preparation method according to claim 1, characterized in that, In step 1, the pore-forming agent is selected from at least one of ammonium bicarbonate, urea, and ammonium oxalate; the transition metal powder is selected from at least one of iron powder, cobalt powder, and nickel powder; the binder is selected from at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, and polyethylene glycol; the average particle size of the boron carbide powder is 10-50 μm; the average particle size of the transition metal powder is 50-200 nm; and the organic solvent is selected from at least one of anhydrous ethanol, methanol, and isopropanol, wherein the amount of organic solvent added is 0.8-1.5 times the total mass of the boron carbide powder, pore-forming agent, transition metal powder, and binder.

3. The preparation method according to claim 1, characterized in that, In step 2, the pressing pressure for the pressure molding is 200~350MPa.

4. The preparation method according to claim 1, characterized in that, The inert gas mentioned in step 3 is argon or nitrogen, and the gas flow rate of the inert gas is 100~300 mL / min.

5. The preparation method according to claim 1, characterized in that, The pre-calcination heating process described in step 3 is as follows: the temperature is increased from room temperature to 350-450°C at a heating rate of 2-5°C / min, and held for 1-3 hours to allow the pore-forming agent to decompose and form interconnected pores; then the temperature is increased to 750-900°C at a heating rate of 3-6°C / min.

6. The preparation method according to claim 1, characterized in that, The secondary sintering process described in step 4 is as follows: the temperature is increased to 450-500℃ at a heating rate of 3-5℃ / min, held for 1-3 hours, then increased to 900-1000℃ at a heating rate of 3-5℃ / min, held for 1-2 hours, and then decreased to 300℃ at a cooling rate of 1-3℃ / min, and then allowed to cool naturally to room temperature.

7. The preparation method according to claim 1, characterized in that, The aluminum powder mentioned in step 4 is industrial pure aluminum powder or aluminum alloy powder, and the average particle size of the aluminum powder is 10~50μm; the particle size of the porous preform after crushing is 1~5mm.

8. The preparation method according to claim 1, characterized in that, The repressing pressure in step 4 is 100~200MPa.

9. An aluminum boron carbide-based composite adsorbent material, characterized in that, The aluminum boron carbide-based composite adsorbent material is prepared by the preparation method described in any one of claims 1 to 8.

10. The application of the aluminum boron carbide-based composite adsorbent material according to claim 9 in the adsorption of gaseous iodine.

Citation Information

Patent Citations

  • Preparation method and application of aluminum boron carbide-based gas adsorption material

    CN120420953A

  • Preparation method and application of aluminum boron carbide composite material

    CN120666189A